Introduction to Microsoft Access 2010 - Miles, Timothy J.; Safari eBooks ([S.l.] : CompuWorks, 2012)
"This course covers the basics functions of Access 2010. After an introduction to database concepts and the Access environment and Help systems, you will learn how to open and use existing databases and design and create databases. Next, you will work with tables, fields, and records; sort, search and filter data; and set field properties and data entry rules. You also will learn to create queries, forms, and reports."--Resource description page.
Title from title screen.
Publication information from resource description page (viewed Apr. 9, 2013).
Presenter, Timothy Miles.
Keywords: Database management; Microsoft Access; Electronic books